Tzedek, Tzedek Tirdof : poetry, prophecy, and justice in Hebrew scripture : essays in honor of Francis Landy on the occasion of his 70th birthday - Landy, Francis.; Gow, Andrew Colin. (Biblical Interpretation Series, 2017)
Tzedek, Tzedek Tirdof: Poetry, Prophecy, and Justice in Hebrew Scripture. Essays in Honor of Francis Landy on the Occasion of his 70th Birthday is a collection of essays by colleagues, friends, and students of Prof. Francis Landy. It is the second Festschrift dedicated to this remarkable teacher and colleague, friend and mentor, and thus bears witness to the remarkable esteem in which Prof. Landy is held in the Biblical Studies community and beyond (including literary studies, film studies, and poetry).